A Double-Blind, Randomized Controlled Trial of Hydroxychloroquine for Cognitive Dysfunction and Inflammatory Biomarkers in Systemic Lupus Erythematosus Patients in Indonesia - Bantar Suntoko; Suharyo Hadisaputro; Handono Kalim; Suyanto Hadi; Ika Vemilia Warlisti (Indonesian Biomedical Journal, 2023)
BACKGROUND: Systemic lupus erythematosus (SLE) is an autoimmune condition characterized by persistent, chronic inflammation that damages organ tissue. One of the symptoms that is often found in SLE is cognitive dysfunction. Hydroxychloroquine is recommended for the treatment of all levels of SLE. This study was conducted to prove the influence of hydroxychloroquine on improving cognitive function and inflammatory biomarkers compared to standard therapy.